2011
DOI: 10.4274/jcrpe.v3i3.28
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Increase in Carotid Artery Intima-Media Thickness in Infants of Diabetic Mothers

Abstract: Objective: Infants of diabetic mothers (IDM) are considered as a risk group for atherosclerosis. Increased aortic intima-media thickness has been reported in IDM. The purpose of this study was to assess carotid artery intima-media thickness (CA-IMT), left ventricular mass index (LVMI) and atherosclerotic risk factors in IDM. Methods: Thirty IDM and 25 healthy controls were included in the study. Of these infants, 14 were appropriate-for-gestational age (AGA) and 16 were large-for-gestational age (LGA). CA-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…In the other study, non-breastfed children on formulas with higher protein content during their first year of life had a lower CIMT (SMD −0.21 (95% CI: −0.45 to 0.04)) compared to children on lower protein formulas [ 63 ]. Scarce evidence, reported in 1 study, existed for other factors, such as cardio-metabolic and inflammatory factors, for instance, blood pressure [ 81 ], cord blood cholesterol [ 55 ], cortisol [ 69 ], and epigenetic changes, such as DNA methylation levels following exposure to air pollution [ 56 , 57 ] (Tables 1 and S6 ).…”
Section: Resultsmentioning
confidence: 98%
“…In the other study, non-breastfed children on formulas with higher protein content during their first year of life had a lower CIMT (SMD −0.21 (95% CI: −0.45 to 0.04)) compared to children on lower protein formulas [ 63 ]. Scarce evidence, reported in 1 study, existed for other factors, such as cardio-metabolic and inflammatory factors, for instance, blood pressure [ 81 ], cord blood cholesterol [ 55 ], cortisol [ 69 ], and epigenetic changes, such as DNA methylation levels following exposure to air pollution [ 56 , 57 ] (Tables 1 and S6 ).…”
Section: Resultsmentioning
confidence: 98%
“…Smaller arterial lumen diameters (LDs) and reduced microvasculature have also been reported in this population. 22 In LGA neonates, both increased 23,24 and appropriate 25 IMTs have been reported. This suggests a nonlinear U-shaped association between intrauterine body and arterial growth.…”
Section: See Editorial By Gardiner See Clinical Perspectivementioning
confidence: 99%
“…Atabek et al demonstrated that there was no significant difference in the cIMT in neonates of diabetic mothers as compared to controls. 15 This study had a very small sample size and thus was heavily underpowered. The present study, despite being adequately powered, did not show a difference in cIMT between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Based on these, a sample size of 65 children in each group for E/E 0 was calculated (using World Health Organisation sample size calculator version 2.0) to enable us to observe a 20% difference between the exposed and unexposed groups, with 90% power and 5% level of significance. This sample size would also be adequate to detect a difference in cIMT 15 based on the given assumptions.…”
mentioning
confidence: 99%